MODUL PEMBELAJARAN KIMIA SMA KELAS XI PADA POKOK BAHASAN ASAM BASA - Fidella Trixie; Nofri Yuhelman; Jumriana Rahayu Ningsih (Universitas Islam Kuantan Singingi, 2023)
The Purpose of this study is know the worthiness of idleness the module asa learning medium on acidic materials for high scholl SMA/MA classes XI. This method of research is (research and development, R&D) with ADDIE development model which includes the stages of analyze, design, development, implementation, evaluation. The data gathering instruments used are through the validation sheets of media experts, material experts, linguists, and student responses sheets. Technical data analysis used is by calculating the validation percentage score. Research shows that the learning media module developed meets the appropriate categories of media experts by 93,51%, material experts by 79,16%, and language experts by 87,5%. This learning media also meets the appropriate category with a percentage of 82,72%.